MANAJEMEN KURIKULUM DALAM RANGKA PELAYANAN PEMBELAJARAN DAN PENINGKATAN KOMPETENSI PESERTA DIDIK DI SMPN 1 KEDUNGWARINGIN - M Aidil Novian Maskur; Hinggil Permana; Chairil Fajar Hadiansyah (STKIP Pesisir Selatan, 2026)
Curriculum management is an essential part of improving the quality of education and student competency. The purpose of this study is to describe the various approaches used by SMPN 1 Kedungwaringin to manage the curriculum with the aim of improving learning services and enhancing student competencies. A descriptive qualitative method was used in this study, collecting data through observation, interviews, and documentation. The results show that there are four main stages: planning, organizing, implementing, and monitoring and evaluation used to manage the curriculum at SMPN 1 Kedungwaringin. In the planning stage, teachers frequently participate in training and MGMP, teachers also create daily agendas and teaching modules. In the organizing stage, tasks are divided according to teacher abilities and take into account students' religious diversity. The curriculum is implemented through active, creative, and project-based learning with enrichment and improvement programs. Monitoring and evaluation are carried out through the principal's supervision, digital attendance, and learning evaluation. This study found that a systematic curriculum management strategy can optimally improve learning services and student competencies.